Evaluation of perishability in cassava roots (Manihot esculenta Crantz) variety INIAP P-652 by pre-harvest pruning - Pico Moreira, Cristina Marisol (2025)
Cassava (Manihot esculenta Crantz) is an important crop for small farmers in the province of Manabí, due to its prominence in ecuadorian cuisine, as is one of the main ingredients in local dishes such as encebollado, tortillas, muchines, and others. The high starch content of its roots is related to rapid physiological deterioration, which causes decomposition and loss of nutritional content. This work aims to evaluate the effects of intensity and time pruning before harvest on variety INIAP-P 652 “La Rendidora”, by determining agronomic and productive variables, as well as starch content and shelf-life of the roots. A randomized complete block design (RCBD) with bi-factorial arrangement, 2 x 3 + 1 control (without pruning), with four replications was used. The pruning intensity was carried out by cutting 50 and 75 % of the foliage on plants at 14, 21 and 28 days before harvest. The plants subjected to the pruning intensity at 50 and 75 % showed deterioration symptoms on the fourth day, with values of 13.3 and 3.3 %, respectively. The treatment with 75 % pruning at 28 showed deterioration symptoms on the seventh day. This contrasts with the control plants, which showed deterioration symptoms the day after the harvest. The results suggest that pruning before harvest increases the shelf-life of cassava roots.